Kurikulum Merdeka dalam Pembentukan Karakter Siswa - Richard Daniel Herdi Pangkey; Regina Sarudi (Departement of Mathematics Education, 2024)
Education is the most important part of human life and each must have it because for the survival of every human being or every individual who will come. In today's Indonesia adheres to the curriculum of independent learning where learners have the breadth of determining the achievements undertaken. Likewise, in the problems that are taken, namely the independent curriculum in the formation of student character, that is, for students to be positive, have good morals and control emotions and of course show the attitude of pancasila profile. In this study, data collection techniques are carried out with online references, articles or journals, books and use the data as a source and Conjunction of qualitative research in the form of descriptive data with various types of literature studies research sourced from library research ( library research). And the purpose of the independent curriculum in the formation of character is that students have the character to improve the skills and confidence of students to achieve success, in a creative and innovative pattern by giving students the opportunity to cultivate students in learning and thinking and the last is to develop a religious character includes strong cultural and moral values as a provision to face challenges in competition in the future..